The impact of a comprehensive clinical pharmacist counseling intervention program on patients with chronic illness in India: a quasi-experimental study - Soni, Mehul; Soni, Bhoomi; Parihar, Narendra B.; Rathore, Mahendra S.; Mathur, Medha (International Journal of Research in Medical Sciences, 2026)
Background: Chronic conditions such as cardiovascular disorders, diabetes mellitus, respiratory disorders, and cancer continue to be predominant cause to morbidity and mortality globally. Suboptimal adherence to prescribed medication represents a critical obstacle to achieve optimal therapeutic outcomes and effective disease management. Objective of the study was to assess the effect of a comprehensive clinical pharmacist counseling intervention program (CPCIP) on medication adherence, knowledge, attitudes, practices (KAP), and patient satisfaction among individuals with chronic illnesses in a tertiary care hospital in India. Methods: The quasi-experimental study was conducted with pre and post interventions among patients with chronic diseases at a tertiary care hospital. Clinical pharmacists delivered systematic counseling regarding medication adherence, lifestyle modifications, and disease management strategies. Along with that, the Morisky medication adherence scale (MMAS-8), a validated KAP scale, and satisfaction questionnaires were used before and after the ​‍​‌‍​‍‌​‍​‌‍​‍‌intervention. Results: This study evaluated the CPCIP intervention improved adherence and KAP scores with patient satisfaction, the mean MMAS-8 score significantly increased post intervention from 3.05±1.10 to 5.55±0.95 (p<0.001). The three domains KAP also demonstrated an improvement while patients reported satisfaction level 8.62±0.84 out of 10 scale. There were positive correlations were found among satisfaction, adherence scores, and KAP improvements. Conclusions: The CPCIP effectively enhanced adherence, patient understanding, and satisfaction. Integrating pharmacist-led counseling within routine healthcare services can supports effective chronic disease management, reduce complications, and healthcare burden while improving overall healthcare outcomes in patients with chronic illness in India.